Media Massa dan Demokrasi di Indonesia: Studi Tentang Afiliasi Politik Media Massa dalam Pemilu 2019-2024 - Paramitha, Diandra; Fahadayna, Adhi Cahya (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2024)
The aim of this study is to analyze the level of news distribution about general elections, mass media partisanship, and the impact of media polarization on public sentiment in holding the 2019 and 2024 general elections. This study used a quantitative approach with a descriptive type. The level of news distribution about Presidential and Vice Presidential candidates in the mass media during the 2019 and 2024 general elections has quite significant differences. News distribution during the 2019 general election was only dominated by @VIVAcoid, while in the 2024 general election news distribution was dominated by @VIVAcoid and @officialinews_. Partisan media alignments in the 2019 general election are towards the candidate pair Joko Widodo and Ma'ruf Amin, while in the 2024 general election partisan media alignments are towards the political affiliation of each media. News on @VIVAcoid leads to candidate pair Prabowo Subianto and Gibran Rakabuming Raka, @mediaindonesia leads to candidate pair Anies Baswedan and Muhaimin Iskandar, and @officialinews_ leads to candidate pair Ganjar Pranowo and Moh. Mahfud MD. Media polarization during the 2019 and 2024 general elections gave rise to negative public sentiment.